Codemixing in an Entertainment TV Show: How "Which Is" Functions in Indonesians' Repertoire (NOBEL: Journal of Literature and Language Teaching, 2019)
The present article portrays the use of "which is" as a currently popular mixed-code among Indonesians, especially teenagers and public figures, since the 2010s or popularly named as the language of South-Jakartans (Bahasa Anak Jaksel) by taking an Indonesian TV show as the data collection sites. The data were the comments of one of the judges of Indonesian Idol 2018, pseudonymized as ME. For investigation purpose, videos containing the "which is" phrase uttered by ME were sorted, transcribed, and analyzed. The analysis focused on how "which is" functions in the utterances. It was found that "which is" used by Indonesians likely functions as substituting conjunctions and discourse markers. The substituting conjunctions include cause-effect and coordinating conjunctions, as for the discourse markers function to minimize face-threatening act.